Planning Commercialization of Mobile Laboratory Product Technology Innovation Using Business Model Canvas - Subiyanto; Miranti Budi Kusumawati; Sri Wijayanti; Unik Setiawati (Majalah Ilmiah Pengkajian Industri, 2022)
A premise states that the success of product technology innovation determines the economic growth of a country. On the other hand, commercialization of product technology innovations has low success, and one of the reasons is the lack of careful planning. One of the national product technology innovations designed as a solution to controlling the spread of COVID-19 is a mobile laboratory (Mobile Laboratory Bio-Safety Level 2/MBSL-2) which was initiated by BPPT in early 2020. This study discusses the concept of planning the commercialization of product technology innovations. MBSL-2 uses the Business Model Canvas (BMC), with the intention that the results can be used as an innovation planning policy instrument, especially in government research institutions. Nine BMC elements are elaborated, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structure. The results of the discussion show how BMC works in a systematic, structured, and measurable way so that it can explain the arguments and objectives for each element of the business process, as well as the harmonization of business strategy with technology strategy. The BMC display is simple but contains important business aspects, making it easier for all parties to understand the business concept of product technology innovation. This study recommends the use of BMC as a complete product technology innovation planning instrument for engineers in government research institutions. Keyword: Technological product,  mobile laboratory,  commercialization of product innovations, business model.